O autismo e as práticas de cuidado na atenção básica à saúde: a perspectiva de profissionais - Polli, Letícia Migliatti (2024)
Autism, as a nosological classification, has changed over the decades since the studies of Kanner and Asperger in the 40s. The prevalence has risen significantly every year, raising important debates about care, as well as the pathologization and medicalization of childhood. The history of care for autistic children and adolescents in Brazil was marked by a late start and by disputes between different camps. Even though there are differences of opinion, public policies indicate that Primary Health Care (PHC) is fundamental to the care network. This emphasizes the importance of PHC both for monitoring this population and articulating the intersectoral network, even though the literature points to numerous challenges ranging from a lack of professional training to political direction. That said, it is essential to carry out studies that address the reality of autistic children in the area, from the PHC perspective, with a view to developing effective care strategies to meet their health needs. The general objective of this study was to identify and understand how care practices for autistic children and their families have been operationalized in PHC. The specific objectives were to understand how the team identifies autistic children in the territory and what procedures/strategies are adopted when autism is suspected; to understand what the main challenges and possibilities are in relation to care practices for autistic children and their families in PHC. As for the methodology adopted, this is an exploratory, descriptive study with a qualitative approach. There were 19 participants, including managers and professionals from six teams in the Family Health Units (USF) of a medium-sized municipality in the interior of the state of São Paulo. The instruments used for data collection were two forms - one to identify and characterize the participants and the other to characterize the USF - and a semi-structured interview. Data was collected in person. The data was analyzed using Bardin's categorical analysis. As a result, in relation to the USFs, it was found that all the units had a minimum team of professionals, only half offered activities aimed at children and young people, but which included autism, almost none were mentioned. The majority of the participants are women, from a variety of professional backgrounds. Their activities ranged from general clinical care to preceptorship and management of the Unit. Few reported having previous experience with autism. It was possible to understand that autism is hardly recognized by PHC professionals, with community agents being mentioned as important players in identifying children with suspected autism in the territory. In addition, there is a logic of care centered on referral to specialists, often justified by a lack of professional training. Participants also highlighted the importance of childcare and territorial care for this population and the many challenges to operationalizing care at this level of health care, such as lack of knowledge of existing services and flows, lack of resources and difficulties in articulating the network. This study contributed important elements for the planning and implementation of care strategies for autistic children within the scope of PHC, from the perspective of psychosocial care. In this sense, it is emphasized that the challenges for the operationalization of care remain, as already evidenced in previous studies, and it is necessary to advance so that it is possible to actually guarantee the rights of this population, such as expanded and comprehensive care, school inclusion, based on territorial care practices, access and articulation of the intra and intersectoral network.